Metoda taksonomii wrocławskiej w klasyfikacji obiektów symbolicznych - Dudek, Andrzej (Dendrite Clustering in Classification of Symbolic Objects, 2007)
Dendrite clustering is used in multivariate statistical analysis for over fifty year. Despite it has been designed for "traditional" data, after minor modifications it can be adapted to symbolic data e.g. data representing: single quantitative values, categorical values, intervals, multi-valued variables, multi-valued variables with weights. In this paper usage of dendrite method for symbolic data is described, Nine clustering algorithms: Ward, single link, complete link, average link, Mcquitty, median and centroid hierarchical clustering methods, partitioning around medoids, dynamic clustering for symbolic objects are compared with dendrite method and situations where this method gives better results are pointed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 169-177